Didactic Model in the Teaching-Learning Process at the Higher Education Level - Hernández Muñoz, Donald Ariel (2023)
The main purpose of the research was to create an educational approach to facilitate the learning of physics in a mechanics course at the university level, supported by the use of technological resources and active and participatory didactic approaches appropriate to meet the needs and requirements of the era. current. The study was carried out at the National University of Engineering, specifically at the UNI - North headquarters, located in Estelí, using a mixed approach with a qualitative predominance within the socio-critical paradigm. The sample included a total of 90 students, 5 professors, a coordinator and a director, who were selected using a non-probabilistic and convenience sampling method. To collect data, various techniques were used, such as document analysis, literature review, observation, interviews, matrix analysis, discussion groups and surveys. Based on the findings obtained, a heuristic didactic model was developed with the objective of improving the teaching-learning process of Physics in higher education. This model stands out for its applicability in other disciplines, such as Mathematics. The research concludes that the application of this model can have a significant impact on the promotion of new scientific research in the field of Physics and Mathematics teaching. In summary, this article offers a significant contribution to improving the teaching-learning process in higher education through the introduction of an innovative and flexible heuristic model.